Pengaruh Cash Flow Operating, Leverage, Likuiditas dan Profitabilitas terhadap Financial Distress - Etika Putri, Sinta; Ainiyah, Nur; Ilmiddaviq, Muhammad Bahril (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research is motivated by the drastic decline in stock prices of technology companies in 2022, which reflects heavy financial pressure and deteriorating financial performance until June 2023. This condition raises the potential risk of financial crisis or financial distress. This study aims to examine the effect of cash flow operating, leverage, liquidity, and profitability on financial risk in technology subsector manufacturing companies listed on the IDX during the 2020-2023 period. A quantitative approach with secondary data of company financial reports that have been audited and published by the IDX is used in this study. The purposive sampling technique was applied to select 19 companies as samples from a total of 49 companies. Data analysis was performed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with Smart PLS software. The results of this study indicate that cash flow operating has no significant effect on financial distress (p> 0.05). In contrast, leverage has a significant positive effect (p < 0.05), while liquidity (current ratio) and profitability (ROA) have a significant negative effect on financial distress (p < 0.05). High leverage increases financial risk, while high liquidity and profitability can reduce the risk of financial distress in technology companies.